POLEMIC OF SETTING MINIMUM WAGE OF CITY DISTRICT DURING THE COVID 19 PANDEMIC - Rachmad Abduh (Proceeding International Seminar of Islamic Studies, 2022)
Covid-19 (Corona Virus disase) has hit the world, since December 2019, first tested in the city of Wuhan, Hubei Province china. Due to the Covid-19 virus caused many impacts in all countries, not least in Indonesia. The Indonesian government imposes Large-Scale Social Restrictions (PSBB) and requires that almost all activities be carried out at home. This has an impact on workers because of the psbb related to the income or wages of workers.Recently the City district government has set a minimum wage in 2022. As is known, the basis of setting the minimum wage is based on the Need for Decent Living (KHL) with attention to productivity and economic growth. The need for decent living is used as a basis for determining the minimum wage, which is calculated based on the needs of workers in meeting basic needs that include food, housing, clothing and education.During the Covid-19 pandemic, the need for living is increasing which is not proportional to the income of workers, this is due to the increase in the price of basic goods. Not to mention that Indonesia's economic growth has decreased due to Covid-19, this is related to the establishment of a minimum wage that is determined based on productivity and economic growth